A high-performance self-compacting and highly crack-resistant fiber-reinforced cement-based composite material and its preparation method

By controlling the composition and structure of cement-based composite materials, using chemical bonding of modified geological polymers and nanosilica, and combining with polypropylene fiber mesh structure, the contradiction between flowability and crack resistance of self-finished cement-based composite materials is solved, and the balance of high flowability and crack resistance is achieved, and the comprehensive performance of the material is improved.

CN120136513BActive Publication Date: 2025-07-22HOMOGEN NEW QUALITY (XIAN) NEW MATERIALS CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510609934.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-05-13
Publication Date
2025-07-22
Estimated Expiration
2045-05-13

AI Technical Summary

Technical Problem

The existing self-finished cement matrix composites are difficult to balance between fluidity and crack resistance. High fluidity leads to the separation of aggregates from cement slurry, which has poor crack resistance and is prone to cracking.

Method used

By controlling the bone-gluing ratio, water-gluing ratio and sand ratio, adding modified geological polymers and expansion agents, an organic-inorganic composite structure is formed, combining polypropylene fiber mesh structure, improving fluidity and crack resistance, and reducing friction by using the chemical bonding and smooth structure of nano-silica.

Benefits of technology

The resulting cement-based composite material has excellent fluidity, separating resistance and crack resistance, and improves mechanical properties and durability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

This application relates to the field of cement-based composites, and specifically discloses a high-performance self-compacting and high-crack-resistant fiber-reinforced cement-based composite material and a preparation method thereof. The cement-based composite material comprises the following raw materials: cement, fly ash microspheres, silica fume, modified geopolymers, sand, fine aggregates, polypropylene fibers, expansive agents, admixtures and water; wherein, the admixtures at least comprise xanthan gum. The preparation method comprises the following steps: mixing and stirring cement, fly ash microspheres, silica fume, sand, fine aggregates and modified geopolymers, and adding an expansive agent to obtain a preliminary mixture; mixing the admixtures and water, adding the preliminary mixture, then adding polypropylene fibers, and after stirring and mixing, adding the remaining admixtures and stirring to obtain the product. This application has the characteristics of preparing a cement-based composite material with better fluidity while having better segregation resistance and crack resistance, and can be used in fields such as the bottom plate of the formwork-free floor slab, the grouting reinforcement of the foundation support, the reinforcement by the method of increasing the cross-section, and the rapid repair of the road surface.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of building materials, and more specifically, to a high-performance self-compacting and high-crack-resistant fiber-reinforced cement-based composite material and a preparation method thereof. Background Art

[0002] In the field of building materials, cement-based composite materials, as a widely used engineering composite material, their performance and preparation technologies have always attracted much attention. Among them, self-compacting cement-based composite materials, as an important branch of cement-based composite materials, are widely used in scenarios such as secondary pouring outside the thermal insulation of cement-based composite material walls and parts where vibration is impossible due to dense reinforcement because of their good fluidity and self-compacting property, which can fill the formwork and reach a dense state without external vibration.

[0003] However, with the rapid development of the construction industry and the continuous improvement of the performance requirements of cement-based composite materials in engineering, some deficiencies in the performance of traditional self-compacting cement-based composite materials have gradually emerged. In particular, the contradiction between the self-leveling performance and the state before self-compaction is difficult to reconcile. Specifically, self-leveling requires that the cement-based composite material has extremely high fluidity, but high fluidity easily leads to segregation settlement between the aggregate and the cement paste, thereby affecting the mechanical properties of the cement-based composite material; in addition, due to the high content of fine particles, low water-binder ratio, large drying shrinkage, and poor crack resistance of self-compacting cement-based composite materials, although fibers are added to improve the crack resistance performance at present, it will affect the fluidity.

[0004] Therefore, how to prepare a cement-based composite material with better fluidity while having better anti-segregation and anti-crack properties is of great significance for cement-based composite materials. Summary of the Invention

[0005] In order to prepare a cement-based composite material with better fluidity while having better anti-segregation and anti-crack properties, the present application provides a high-performance self-compacting and high-crack-resistant fiber-reinforced cement-based composite material and a preparation method thereof.

[0006] In the first aspect, the present application provides a high-performance self-compacting and high-crack-resistant fiber-reinforced cement-based composite material and a preparation method thereof, adopting the following technical solutions:

[0007] A high-performance self-compacting and high-crack-resistant fiber-reinforced cement-based composite material, comprising the following raw materials in parts by weight:

[0008] 300 - 400 parts of cement, 50 - 70 parts of fly ash microspheres, 30 - 40 parts of silica fume, 70 - 100 parts of modified geopolymers, 250 - 300 parts of sand, 650 - 700 parts of fine stones, 3 - 12 parts of polypropylene fibers, 3 - 8 parts of expansion agents, 2 - 6 parts of admixtures, and 100 - 120 parts of water;

[0009] Among them, the admixture at least includes xanthan gum. The modified geopolymers are prepared by first subjecting geopolymers to primary modification treatment with a polyurethane prepolymer and water, and then treating them in a modification solution containing ethylene glycol, ethylenediamine, and γ-aminopropyltriethoxysilane, and then loading carboxylated nano-silica.

[0010] By adopting the above technical solution, in this application, through the control of the bone-to-binder ratio, water-to-binder ratio, and sand ratio, the prepared cement-based composite material has good fluidity. The initial slump flow can reach more than 700 mm, and the slump flow after 30 min can reach more than 550 mm. It can achieve demolding in 4 h, and the demolding strength is 20 MPa. In addition, xanthan gum is added to the admixture of this application. As a thickening agent, it can increase the cohesiveness and reduce the tendency of bleeding and segregation, thus having a positive effect on the mechanical properties and durability of the cement-based composite material.

[0011] In addition, on the basis of reducing fly ash microspheres, this application also adds some modified geopolymers. The hydration products in the geopolymers can adsorb and stabilize free water, reduce the bleeding phenomenon, and improve the anti-segregation performance of the cement-based composite material. At the same time, in this application, the geopolymers are first modified with a polyurethane prepolymer and water to form a polyurethane layer on the geopolymers, forming an organic-inorganic composite structure, which can reduce the friction between particles and improve the fluidity of the cement-based composite material. The introduction of polyurethane segments introduces flexibility, reduces the internal friction force of the cement-based composite material, and improves the fluidity. At the same time, the formed core-shell structure has a micro-buffering characteristic, enabling the cement-based composite material to better disperse stress when stressed and inhibiting crack propagation. With the addition of an expansive agent, the expansive agent generates volume expansion after hydration, offsetting the shrinkage stress during the hardening process of the cement-based composite material and reducing the cracking probability. Polypropylene fibers form a network structure in the cement-based composite material, bridging micro-cracks and hindering crack propagation. The combination of the above significantly improves the crack resistance of the cement-based composite material.

[0012] In addition, the geopolymers in this application are also treated in a modification solution containing ethylene glycol, ethylenediamine, and γ-aminopropyltriethoxysilane. Ethylene glycol reacts with unreacted isocyanate groups to form a hydroxyl-containing urethane structure, and the introduction of ethylenediamine introduces amino functional groups onto the modified geopolymer core-shell structure. The treatment with γ-aminopropyltriethoxysilane also introduces amino functional groups. Then, carboxylated nano-silica is loaded and dispersed in the polyurethane prepolymer. The carboxyl functional groups of the nano-silica form chemical bonds with the hydroxyl and amino groups introduced on the surface of the geopolymer core-shell structure, thus being fixed on the surface of the core-shell structure. The high sphericity of the nano-silica forms a coating layer with a certain smooth structure, acting as "micro ball bearings" in the cement-based composite paste to reduce the friction between aggregates, improve fluidity, and at the same time, the carboxylated nano-silica embedded in the core-shell structure of the modified geopolymer forms chemical bonds with the cement hydration products to limit the generation of shrinkage stress and reduce the risk of cracking. Finally, the cement-based composite prepared in this application has excellent fluidity and good anti-segregation performance, thus having better mechanical properties and excellent anti-cracking performance, and improving its durability.

[0013] Optionally, the modified geopolymer is prepared by the following steps:

[0014] S1. Mix the geopolymer with the polyurethane prepolymer, add water, stir, and let it stand to obtain a pre-modified geopolymer.

[0015] S2. Mix ethylene glycol, ethylenediamine, and γ-aminopropyltriethoxysilane with water to obtain a modification solution. Then add the pre-modified geopolymer to the modification solution and impregnate it at 50 - 60 °C for 4 - 6 h, and filter to obtain a functionalized geopolymer.

[0016] S3. Mix carboxylated nano-silica, hydroxypropyl cellulose, and water to obtain a suspension.

[0017] S4. Add the functionalized geopolymer to the suspension, stir at 60 - 70 °C for 1 - 2 h, filter, wash, and dry to obtain the modified geopolymer.

[0018] By adopting the above technical solution, the geopolymer is first mixed and reacted with the polyurethane prepolymer and water. The polyurethane prepolymer and water react to form a flexible polymer network, forming a core-shell structure with high-strength internal geopolymer as a rigid support structure and a flexible polyurethane buffer layer on the outside. The polyurethane layer has a certain buffering performance, alleviates the expansion of cracks, and plays a certain anti-cracking role. Then, subsequent modification solution modification treatment and the loading of carboxylated nano-silica are carried out to achieve the loading of carboxylated nano-silica, which plays a role in improving the fluidity, anti-segregation performance, and anti-cracking performance of the cement-based composite, and improves the performance of the cement-based composite.

[0019] Optionally, during the preparation of the modified geopolymer, the mass ratio of the geopolymer to the polyurethane prepolymer added in step S1 is 1:(0.4 - 0.6), and the addition amount of water is 5 - 10 wt% of the polyurethane prepolymer;

[0020] In step S2, the mass ratio of ethylene glycol, ethylenediamine, γ-aminopropyltriethoxysilane to water added is 1:(1.2 - 1.4):(1.5 - 1.8):(4 - 6), and the mass ratio of the pre-modified geopolymer to the modification liquid added is 1:(4 - 5);

[0021] In step S3, the mass ratio of carboxylated nano-silica, hydroxypropyl cellulose to water added is 1:(0.1 - 0.2):(2 - 3);

[0022] In step S4, the mass ratio of the functionalized geopolymer to the suspension added is 1:(3 - 4).

[0023] By adopting the above technical solution, through the control of the addition of each raw material, the comprehensive performance of the finally prepared cement-based composite material is better.

[0024] Optionally, the carboxylated nano-silica in step S3 is prepared by the following method:

[0025] The nano-silica is treated in a sulfuric acid solution with a mass concentration of 65 - 75% for 5 - 10 min and then dried to obtain pretreated nano-silica;

[0026] Acrylic acid and succinic acid are mixed with xylene according to a mass ratio of 1:(1 - 1.2):(2 - 2.2) to obtain an organic acid solution, and then concentrated sulfuric acid is added. The addition amount of concentrated sulfuric acid is 0.5 - 1 wt% of the organic acid solution to obtain a mixed acid solution. Then, the pretreated nano-silica is added to the mixed acid solution, and reflux reaction is carried out at 80 - 100 °C for 2 - 3 h. After centrifugal separation, it is washed with water and alcohol and then dried to obtain carboxylated nano-silica. The mass ratio of the pretreated nano-silica to the mixed acid solution added is 1:(0.3 - 0.5).

[0027] By adopting the above technical solution, the nano-silica is first treated in a sulfuric acid solution to enhance the activity of the surface hydroxyl groups, and then acrylic acid and succinic acid are used as reaction substances, and concentrated sulfuric acid is used as a catalyst to introduce carboxyl functional groups through the esterification reaction of the hydroxyl groups of the nano-silica, realizing the carboxylation treatment of the nano-silica.

[0028] Optionally, the polypropylene fiber is added after being modified, and the modification treatment includes the following steps:

[0029] 1), The polypropylene fiber is treated by plasma in an oxygen atmosphere to obtain pretreated polypropylene fiber;

[0030] 2), impregnate the prepared pretreated polypropylene fibers in an ethanol aqueous solution added with γ-aminopropyltriethoxysilane, adjust the pH to 4-5, and treat at 60-80 °C for 30-40 min to obtain a pretreated reaction solution;

[0031] 3), add epichlorohydrin to the pretreated reaction solution, react at 60-70 °C for 60-90 min, then cool, filter, wash and dry to obtain modified polypropylene fibers.

[0032] By adopting the above technical solution, the polypropylene fibers are first pretreated by plasma bombardment to introduce oxygen-containing functional groups such as hydroxyl and carboxyl groups, then dehydrated and condensed to introduce amino groups after treatment in an amino silane coupling agent, and then epichlorohydrin is added. The lone pair electrons of the amino group attack the epoxy group in epichlorohydrin to open the ring to form an oxygen anion intermediate, and then a nucleophilic substitution reaction occurs with the hydroxyl group. Finally, epoxy groups are introduced on the surface of the polypropylene fibers. The epoxy groups in the polypropylene fibers react with active hydrogens such as amino groups in the modified geopolymer to form a cross-linked structure, thereby realizing the cross-linking between the polypropylene fibers and the modified geopolymer. This not only helps to improve the cohesiveness of the cement-based composite and improve the bleeding and segregation performance, but also significantly enhances the crack resistance of the cement-based composite, and the prepared cement-based composite has better comprehensive performance.

[0033] Optionally, when the polypropylene fibers are modified, in step 1), the power during plasma treatment is 100-200 W, and the treatment time is 3-6 min;

[0034] In step 2), the addition amount of γ-aminopropyltriethoxysilane is 3-5 wt% of the addition amount of the pretreated polypropylene fibers, and the mass ratio of γ-aminopropyltriethoxysilane to the ethanol aqueous solution is 1:(8-10), and the volume ratio of ethanol to water in the ethanol aqueous solution is 7:(3-4);

[0035] In step 3), the addition amount of epichlorohydrin is 5-8 wt% of the addition amount of the pretreated polypropylene fibers.

[0036] Optionally, when the polypropylene fibers are modified, after adding epichlorohydrin and reacting in step 3), polyacrylamide, PAMAM and genipin with a mass ratio of 1:(1.2-1.4):(0.1-0.2) are also added, and the addition amount of polyacrylamide is 3-5 wt% of the pretreated polypropylene fibers.

[0037] By adopting the above technical solutions, when the polypropylene fiber is modified, polyacrylamide, PAMAM and genipin are also added. PAMAM has a highly branched three-dimensional structure. Its amino groups can not only form chemical bonds with functional groups such as hydroxyl and amino groups on the polypropylene fiber, but also form chemical bonds with functional groups such as hydroxyl groups in the modified geopolymers. Coupled with the addition of genipin, crosslinking between polyacrylamide and PAMAM is achieved. In this way, not only the crosslinked structure between the polypropylene fiber and the modified geopolymer is realized, but the addition of polyacrylamide improves the adhesion of the cement-based composite paste, promotes the physical adhesion between the fiber and the cement matrix, and moreover, the amide groups on its molecular chain form hydrogen bonds with the cement hydration products, enhancing the chemical bonding force in the interfacial transition zone. And by using it to adjust the rheological properties, while maintaining good fluidity, bleeding and segregation phenomena are reduced. The three-dimensional structure of PAMAM can also form multi-point anchoring on the surface of cement particles, improving the mechanical interlocking between the fiber and the matrix, and ultimately enhancing the performance of the cement-based composite material.

[0038] Optionally, the admixture includes welan gum, trimethylolpropane, polycarboxylate water reducer and retarder with a mass ratio of 1:(0.6 - 0.8):(1.2 - 1.4):(0.2 - 0.3).

[0039] By adopting the above technical solutions, the hydroxyl groups of trimethylolpropane react with the isocyanate groups of polyurethane and the amide groups of polyacrylamide to form a three-dimensional network structure, improving the toughness and crack resistance of the cement-based composite material.

[0040] Optionally, the sand selected is manufactured sand with a diameter of 2 - 10 mm, and the fine stone selected is fine stone with a size of 2 - 5 mm.

[0041] In a second aspect, the present application provides a preparation method of a high-performance self-compacting and high crack-resistant fiber-reinforced cement-based composite material, adopting the following technical solutions:

[0042] A preparation method of a high-performance self-compacting and high crack-resistant fiber-reinforced cement-based composite material includes the following steps:

[0043] Mix cement, fly ash microspheres, silica fume, sand, fine stone and modified geopolymer by stirring, and then add an expansion agent to obtain a preliminary mixture;

[0044] Mix 1 / 3 - 1 / 2 of the admixture with water, then add the preliminary mixture and then add polypropylene fibers, stir and mix, and then add the remaining admixture and stir to obtain a high-performance self-compacting and high crack-resistant fiber-reinforced cement-based composite material.

[0045] By adopting the above technical solutions, the method provided by this application is simple, convenient and easy to industrialize. Moreover, the additives in this application are added in two parts. The xanthan gum in the additives is added initially to form an initial lubricating layer, and the other part is added in the later stage of stirring as a stabilizer to prevent the settlement of aggregates. Finally, the prepared cement-based composite material has better performance.

[0046] In summary, this application has the following beneficial effects:

[0047] 1. On the basis of reducing fly ash microspheres in this application, some modified geopolymers are also added. The hydration products in the geopolymers can adsorb and stabilize free water, reduce bleeding phenomenon, and improve the anti-segregation performance of the cement-based composite material. At the same time, in this application, the geopolymer is first modified by a polyurethane prepolymer and water to form a polyurethane layer on the geopolymer, forming an organic-inorganic composite structure, which can reduce the friction between particles, improve the fluidity of the cement-based composite material. The introduction of polyurethane chain segments introduces flexibility, reduces the internal friction force of the cement-based composite material, and improves the fluidity. At the same time, the formed core-shell structure has a micro-buffer characteristic, enabling the cement-based composite material to better disperse stress when stressed and inhibiting crack propagation. With the addition of an expansive agent, the expansive agent generates volume expansion after hydration, offsetting the shrinkage stress during the hardening process of the cement-based composite material and reducing the cracking probability. The polypropylene fibers form a network structure in the cement-based composite material, bridging micro-cracks and hindering crack propagation. The combination of the above significantly improves the anti-cracking performance of the cement-based composite material;

[0048] 2. The geopolymer in this application is also treated in a modification solution containing ethylene glycol, ethylenediamine, and γ-aminopropyltriethoxysilane. Ethylene glycol reacts with the unreacted isocyanate groups to form a hydroxyl-containing urethane structure, and the introduction of ethylenediamine introduces amino functional groups on the core-shell structure of the modified geopolymer. The treatment with γ-aminopropyltriethoxysilane introduces amino functional groups, and then carboxylated nano-silica is loaded and dispersed in the polyurethane prepolymer. The carboxyl functional groups of the nano-silica form chemical bonds with the hydroxyl and amino groups introduced on the surface of the geopolymer core-shell structure, thus being fixed on the surface of the core-shell structure. The high sphericity of the nano-silica is used to form a coating layer with a certain smooth structure, acting as "miniature ball bearings" in the cement-based composite material slurry to reduce the friction between aggregates and improve the fluidity. At the same time, carboxylated nano-silica is embedded in the core-shell structure of the modified geopolymer and forms chemical bonds with the cement hydration products, restricting the generation of shrinkage stress and reducing the cracking risk. Finally, the prepared cement-based composite material in this application has excellent fluidity and good anti-segregation performance, thus having better mechanical properties and excellent anti-cracking performance, and improving its durability. Detailed implementation manners

[0049] The present application will be further described in detail below in conjunction with embodiments. It should be specifically noted that: for those not specifying specific conditions in the following embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. Unless otherwise specified, the raw materials used in the following embodiments can all be obtained from ordinary commercial sources.

[0050] In the following embodiments, the polycarboxylate superplasticizer used is the polycarboxylate superplasticizer with the model CP1200 produced by Nanjing Xinyi Synthetic Technology Co., Ltd.

[0051] The retarder used is sodium tripolyphosphate;

[0052] The xanthan gum used is the xanthan gum produced by Hebei Qiansheng Biotechnology Co., Ltd.

[0053] In the following preparation examples, the polyurethane prepolymer used is the polyurethane prepolymer produced by Hubei Yamaide Biopharmaceutical Co., Ltd., and its -NCO content is 7.8%.

[0054] The geopolymers in the following preparation examples are prepared by the following method:

[0055] 80 g of sodium hydroxide and 100 g of water glass are mixed to prepare an alkali activator, and then it is mixed with 500 g of fly ash, and 100 g of water is added, and after stirring, it is cured for 24 h to obtain a fly ash-based geopolymer.

[0056] The following preparation example is a preparation example of a modified geopolymer

[0057] Preparation Example 1

[0058] A preparation method of a modified geopolymer, comprising the following steps:

[0059] S1. Mix the geopolymer and the polyurethane prepolymer according to a mass ratio of 1:0.5, add water, stir, and let stand to obtain a pre-modified geopolymer. The addition amount of water is 8 wt% of the polyurethane prepolymer;

[0060] S2. Mix ethylene glycol, ethylenediamine, and γ-aminopropyltriethoxysilane with water according to a mass ratio of 1:1.3:1.6:5 to obtain a modification liquid, then add the pre-modified geopolymer to the modification liquid and immerse it at 55 °C for 5 h, and filter to obtain a functionalized geopolymer. The addition mass ratio of the pre-modified geopolymer to the modification liquid is 1:4.5;

[0061] S3. Mix carboxylated nano-silica, hydroxypropyl cellulose, and water according to a mass ratio of 1:0.1:2.5 to obtain a suspension;

[0062] Among them, the carboxylated nano-silica is prepared by the following method:

[0063] The pretreated nano-silica was prepared by treating nano-silica in a sulfuric acid solution with a mass concentration of 70% for 8 min, followed by filtration, separation, and drying. The addition amount of the sulfuric acid solution was 2.5 mass times that of the nano-silica;

[0064] Acrylic acid, succinic acid, and xylene were mixed in a mass ratio of 1:1.1:2.1 to prepare an organic acid solution. Then, concentrated sulfuric acid was added, and the addition amount of the concentrated sulfuric acid was 0.8 wt% of the organic acid solution to obtain a mixed acid solution. Then, the pretreated nano-silica was added to the mixed acid solution, and the mixture was refluxed at 90 °C for 2.5 h. After centrifugal separation, it was washed with water and alcohol and then dried to obtain carboxylated nano-silica. The addition mass ratio of the pretreated nano-silica to the mixed acid solution was 1:0.4;

[0065] S4. The functionalized geopolymer was added to the suspension, stirred at 65 °C for 1.5 h, filtered, washed with water, and dried to obtain the modified geopolymer. The addition mass ratio of the functionalized geopolymer to the suspension was 1:3.5.

[0066] Preparation Example 2

[0067] A preparation method of a modified geopolymer, comprising the following steps:

[0068] S1. The geopolymer and the polyurethane prepolymer were mixed in a mass ratio of 1:0.4, water was added, and the mixture was stirred and left to stand to obtain a pre-modified geopolymer. The addition amount of water was 5 wt% of the polyurethane prepolymer;

[0069] S2. Ethylene glycol, ethylenediamine, and γ-aminopropyltriethoxysilane were mixed with water in a mass ratio of 1:1.2:1.5:4 to obtain a modified solution. Then, the pre-modified geopolymer was added to the modified solution, and the mixture was impregnated at 50 °C for 6 h and then filtered to obtain the functionalized geopolymer. The addition mass ratio of the pre-modified geopolymer to the modified solution was 1:4;

[0070] S3. Carboxylated nano-silica, hydroxypropyl cellulose, and water were mixed in a mass ratio of 1:0.1:2 to prepare a suspension;

[0071] Among them, the carboxylated nano-silica was prepared by the following method:

[0072] The pretreated nano-silica was prepared by treating nano-silica in a sulfuric acid solution with a mass concentration of 65% for 10 min, followed by filtration, separation, and drying. The addition amount of the sulfuric acid solution was 2 mass times that of the nano-silica;

[0073] Mix acrylic acid and succinic acid with xylene in a mass ratio of 1:1:2 to obtain an organic acid solution, then add concentrated sulfuric acid, and the addition amount of concentrated sulfuric acid is 0.5 wt% of the organic acid solution to obtain a mixed acid solution. Then add pretreated nano-silica to the mixed acid solution, reflux and react at 80 °C for 3 h, and after centrifugal separation, wash with water, wash with alcohol and then dry to obtain carboxylated nano-silica. The addition mass ratio of the pretreated nano-silica to the mixed acid solution is 1:0.3;

[0074] S4. Add the functionalized geopolymer to the suspension, stir at 60 °C for 2 h, filter, wash with water and dry to obtain the modified geopolymer. The addition mass ratio of the functionalized geopolymer to the suspension is 1:3.

[0075] Preparation Example 3

[0076] A preparation method of a modified geopolymer, comprising the following steps:

[0077] S1. Mix the geopolymer and the polyurethane prepolymer in a mass ratio of 1:0.6, add water, stir, and stand to obtain a pre-modified geopolymer. The addition amount of water is 10 wt% of the polyurethane prepolymer;

[0078] S2. Mix ethylene glycol, ethylenediamine, and γ-aminopropyltriethoxysilane with water in a mass ratio of 1:1.4:1.8:6 to obtain a modification solution. Then add the pre-modified geopolymer to the modification solution and impregnate at 60 °C for 4 h, and filter to obtain the functionalized geopolymer. The addition mass ratio of the pre-modified geopolymer to the modification solution is 1:5;

[0079] S3. Mix carboxylated nano-silica, hydroxypropyl cellulose and water in a mass ratio of 1:0.2:3 to obtain a suspension;

[0080] Among them, the carboxylated nano-silica is prepared by the following method:

[0081] Treat nano-silica in a sulfuric acid solution with a mass concentration of 75% for 5 min, then filter and separate and dry to obtain pretreated nano-silica. The addition amount of the sulfuric acid solution is 3 mass multiples of the nano-silica;

[0082] Mix acrylic acid and succinic acid with xylene in a mass ratio of 1:1.2:2.2 to obtain an organic acid solution, then add concentrated sulfuric acid, and the addition amount of concentrated sulfuric acid is 1 wt% of the organic acid solution to obtain a mixed acid solution. Then add pretreated nano-silica to the mixed acid solution, reflux and react at 100 °C for 2 h, and after centrifugal separation, wash with water, wash with alcohol and then dry to obtain carboxylated nano-silica. The addition mass ratio of the pretreated nano-silica to the mixed acid solution is 1:0.5;

[0083] S4. Add the functionalized geopolymer into the suspension, stir and process at 70 °C for 1 h, filter, wash with water and dry to obtain the modified geopolymer. The added mass ratio of the functionalized geopolymer to the suspension is 1:4.

[0084] Comparative Preparation Example 1

[0085] A preparation method of a modified geopolymer is carried out according to the method in Preparation Example 1, except that step S1 treatment is not carried out, and the geopolymer is directly subjected to step S2 treatment.

[0086] Comparative Preparation Example 2

[0087] A preparation method of a modified geopolymer is carried out according to the method in Preparation Example 1, except that step S2 treatment is not carried out, and the pretreated geopolymer obtained in step S1 is directly subjected to steps S3 and S4 treatment.

[0088] Comparative Preparation Example 3

[0089] A preparation method of a modified geopolymer is carried out according to the method in Preparation Example 1, except that steps S3 and S4 treatment are not carried out, and the geopolymer after being treated with the modification liquid in step S2 is directly used as the modified geopolymer.

[0090] Example 1

[0091] A preparation method of a high-performance self-compacting and high crack-resistance fiber-reinforced cement-based composite material includes the following steps:

[0092] Mix and stir 350 kg of cement, 60 kg of fly ash cenospheres, 35 kg of silica fume, 280 kg of sand, 680 kg of fine aggregates and 80 kg of the modified geopolymer obtained in Preparation Example 1, and then add 5 kg of an expansive agent to obtain a preliminary mixture;

[0093] Mix 2 kg of an admixture with 110 kg of water, then add the preliminary mixture and then add 8 kg of polypropylene fibers, stir and mix, and then add 2 kg of the admixture and stir to obtain a high-performance self-compacting and high crack-resistance fiber-reinforced cement-based composite material.

[0094] Among them, the fly ash cenospheres are specifically selected as fly ash float beads, the sand is selected as manufactured sand with a diameter of 2 - 10 mm, the fine aggregates are selected as fine aggregates with a size of 2 - 5 mm, the expansive agent is selected as calcium sulfoaluminate-based expansive agent (specifically HEA expansive agent), the admixture is selected as welan gum, trimethylolpropane, polycarboxylate superplasticizer and retarder with a mass ratio of 1:0.7:1.3:0.2, and the cement is selected as 250 kg of 52.5-grade ordinary Portland cement and 100 kg of sulfoaluminate cement.

[0095] Example 2

[0096] A preparation method of a high-performance self-compacting and highly crack-resistant fiber-reinforced cement-based composite material, comprising the following steps:

[0097] Mix 300 kg of cement, 50 kg of fly ash cenospheres, 30 kg of silica fume, 250 kg of sand, 650 kg of fine aggregates and 70 kg of the modified geopolymer prepared in Preparation Example 2 by stirring, and then add 3 kg of an expansive agent to obtain a preliminary mixture;

[0098] Mix 1 kg of an admixture with 100 kg of water, then add it to the preliminary mixture, add 3 kg of polypropylene fibers, stir and mix, and then add the remaining admixture and stir to obtain a high-performance self-compacting and highly crack-resistant fiber-reinforced cement-based composite material.

[0099] Among them, the fly ash cenospheres are specifically selected as fly ash float beads, the sand is selected as machine-made sand with a diameter of 2 - 10 mm, the fine aggregates are selected as fine aggregates with a diameter of 2 - 5 mm, the expansive agent is selected as a calcium sulfoaluminate-based expansive agent (specifically HEA expansive agent), the admixture is selected as welan gum, trimethylolpropane, polycarboxylate water reducer and retarder with a mass ratio of 1: 0.6: 1.2: 0.2, and the cement is selected as 220 kg of 52.5-grade ordinary Portland cement and 80 kg of sulfoaluminate cement.

[0100] Example 3

[0101] A preparation method of a high-performance self-compacting and highly crack-resistant fiber-reinforced cement-based composite material, comprising the following steps:

[0102] Mix 400 kg of cement, 70 kg of fly ash cenospheres, 40 kg of silica fume, 300 kg of sand, 700 kg of fine aggregates and 100 kg of the modified geopolymer prepared in Preparation Example 3 by stirring, and then add 8 kg of an expansive agent to obtain a preliminary mixture;

[0103] Mix 2 kg of an admixture with 120 kg of water, then add it to the preliminary mixture, add 12 kg of polypropylene fibers, stir and mix, and then add 4 kg of the admixture and stir to obtain a high-performance self-compacting and highly crack-resistant fiber-reinforced cement-based composite material.

[0104] Among them, the fly ash cenospheres are specifically selected as fly ash float beads, the sand is selected as machine-made sand with a diameter of 2 - 10 mm, the fine aggregates are selected as fine aggregates with a diameter of 2 - 5 mm, the expansive agent is selected as a calcium sulfoaluminate-based expansive agent (specifically HEA expansive agent), the admixture is selected as welan gum, trimethylolpropane, polycarboxylate water reducer and retarder with a mass ratio of 1: 0.8: 1.4: 0.3, and the cement is selected as 250 kg of 52.5-grade ordinary Portland cement and 100 kg of sulfoaluminate cement.

[0105] Example 4

[0106] A preparation method of a high-performance self-compacting and highly crack-resistant fiber-reinforced cement-based composite material is carried out according to the method in Example 1, except that the polypropylene fiber is added after being modified. The specific operation of the modification treatment is as follows:

[0107] 1), The polypropylene fiber is treated by plasma in an oxygen atmosphere for 5 minutes to obtain pretreated polypropylene fiber, and the power during plasma treatment is 150 W;

[0108] 2), The obtained pretreated polypropylene fiber is impregnated in an ethanol aqueous solution (prepared by mixing ethanol and water according to a volume ratio of 7:3) containing γ-aminopropyltriethoxysilane for 40 minutes, the pH is adjusted to 4.5, and it is treated at 70 °C for 35 minutes to obtain a pretreated reaction solution, where the addition amount of γ-aminopropyltriethoxysilane is 4 wt% of the addition amount of the pretreated polypropylene fiber, and the addition mass ratio of γ-aminopropyltriethoxysilane to the ethanol aqueous solution is 1:9;

[0109] 3), Epichlorohydrin is added to the pretreated reaction solution, and the addition amount of epichlorohydrin is 6 wt% of the addition amount of the pretreated polypropylene fiber. The reaction is carried out at 65 °C for 70 minutes, and then after cooling, it is filtered, washed with water and dried to obtain modified polypropylene fiber.

[0110] Example 5

[0111] A preparation method of a high-performance self-compacting and highly crack-resistant fiber-reinforced cement-based composite material is carried out according to the method in Example 1, except that the polypropylene fiber is added after being modified. The specific operation of the modification treatment is as follows:

[0112] 1), The polypropylene fiber is treated by plasma in an oxygen atmosphere for 6 minutes to obtain pretreated polypropylene fiber, and the power during plasma treatment is 100 W;

[0113] 2), The obtained pretreated polypropylene fiber is impregnated in an ethanol aqueous solution (prepared by mixing ethanol and water according to a volume ratio of 7:3) containing γ-aminopropyltriethoxysilane for 30 minutes, the pH is adjusted to 4, and it is treated at 60 °C for 40 minutes to obtain a pretreated reaction solution, where the addition amount of γ-aminopropyltriethoxysilane is 3 wt% of the addition amount of the pretreated polypropylene fiber, and the addition mass ratio of γ-aminopropyltriethoxysilane to the ethanol aqueous solution is 1:8;

[0114] 3), Epichlorohydrin is added to the pretreated reaction solution, and the addition amount of epichlorohydrin is 5 wt% of the addition amount of the pretreated polypropylene fiber. The reaction is carried out at 60 °C for 90 minutes, and then after cooling, it is filtered, washed with water and dried to obtain modified polypropylene fiber.

[0115] Example 6

[0116] A preparation method of a high-performance self-compacting and highly crack-resistant fiber-reinforced cement-based composite material is carried out according to the method in Example 1, with the difference that the polypropylene fiber is added after being modified. The specific operation of the modification treatment is as follows:

[0117] 1), The polypropylene fiber is treated by plasma in an oxygen atmosphere for 3 min to obtain pretreated polypropylene fiber, and the power during plasma treatment is 200 W;

[0118] 2), The obtained pretreated polypropylene fiber is impregnated in an ethanol aqueous solution (prepared by mixing ethanol and water according to a volume ratio of 7:4) containing γ-aminopropyltriethoxysilane for 50 min, the pH is adjusted to 5, and it is treated at 80 °C for 30 min to obtain a pretreated reaction solution. The addition amount of γ-aminopropyltriethoxysilane is 5 wt% of the addition amount of the pretreated polypropylene fiber, and the mass ratio of γ-aminopropyltriethoxysilane to the ethanol aqueous solution is 1:10;

[0119] 3), Epichlorohydrin is added to the pretreated reaction solution, and the addition amount of epichlorohydrin is 8 wt% of the addition amount of the pretreated polypropylene fiber. It reacts at 70 °C for 60 min, and then after cooling, it is filtered, washed with water and dried to obtain modified polypropylene fiber.

[0120] Example 7

[0121] A preparation method of a high-performance self-compacting and highly crack-resistant fiber-reinforced cement-based composite material is carried out according to the method in Example 4, with the difference that when the polypropylene fiber is modified, after adding epichlorohydrin in step 3) and reacting at 65 °C for 70 min, polyacrylamide, PAMAM and genipin with a mass ratio of 1:1.2:0.1 are also added, and after continuing to react for 60 min, it is cooled, filtered, washed with water and dried to obtain modified polypropylene fiber, and the addition amount of polyacrylamide is 3 wt% of the pretreated polypropylene fiber.

[0122] Example 8

[0123] A preparation method of a high-performance self-compacting and highly crack-resistant fiber-reinforced cement-based composite material is carried out according to the method in Example 4, with the difference that when the polypropylene fiber is modified, after adding epichlorohydrin in step 3) and reacting at 65 °C for 70 min, polyacrylamide, PAMAM and genipin with a mass ratio of 1:1.4:0.2 are also added, and after continuing to react for 60 min, it is cooled, filtered, washed with water and dried to obtain modified polypropylene fiber, and the addition amount of polyacrylamide is 5 wt% of the pretreated polypropylene fiber.

[0124] Example 9

[0125] A preparation method of a high-performance self-compacting and highly crack-resistant fiber-reinforced cement-based composite material is carried out according to the method in Example 7, except that polyacrylamide is not added.

[0126] Example 10

[0127] A preparation method of a high-performance self-compacting and highly crack-resistant fiber-reinforced cement-based composite material is carried out according to the method in Example 7, except that PAMAM and genipin are not added.

[0128] Comparative Examples 1-3

[0129] A preparation method of a high-performance self-compacting and highly crack-resistant fiber-reinforced cement-based composite material is carried out according to the method in Example 1, except that the modified geopolymers are respectively selected from the modified geopolymers prepared in Comparative Preparation Examples 1-3.

[0130] Comparative Example 4

[0131] A preparation method of a high-performance self-compacting and highly crack-resistant fiber-reinforced cement-based composite material is carried out according to the method in Example 1, except that the modified geopolymers are replaced with geopolymers in equal amounts.

[0132] Comparative Example 5

[0133] A preparation method of a high-performance self-compacting and highly crack-resistant fiber-reinforced cement-based composite material is carried out according to the method in Example 1, except that the modified geopolymers are replaced with fly ash microspheres in equal amounts.

[0134] Comparative Example 6

[0135] A preparation method of a high-performance self-compacting and highly crack-resistant fiber-reinforced cement-based composite material is carried out according to the method in Example 1, except that the xanthan gum in the admixture is replaced with a polycarboxylate water reducer in equal amounts.

[0136] Performance testing

[0137] The fluidity, crack resistance and segregation resistance of the cement-based composites prepared in the examples and comparative examples of this application are tested. Among them, the segregation resistance is tested by the bleeding rate through GB / T50080-2016 "Standard Test Method for Properties of Ordinary Cement-Based Composite Mixes", the fluidity is characterized by the initial slump flow and the 30-min slump flow, and the crack resistance is determined by the cracking time through the ring test method. The statistical results are shown in Table 1 below.

[0138] Table 1:

[0139]

[0140] Referring to the test results in Table 1 above, the cement-based composite material prepared in the embodiments of the present application has excellent fluidity, good segregation resistance, and excellent crack resistance, and can be used in fields such as the bottom plate (2 cm) of the non-removable formwork floor slab, the grouting reinforcement of the foundation support, the reinforcement by the method of increasing the cross-section, and the rapid repair of the road surface. Referring to the test results of Example 1 and Examples 4-6, when the polypropylene fiber is added after being modified, its segregation resistance and crack resistance are further improved on the basis of maintaining its fluidity. After the polypropylene fiber is modified, it can interact with the modified geopolymer and cement mortar to improve its segregation resistance and crack resistance. Combining the test results of Examples 7-8, when polyacrylamide, PAMAM, and genipin are added during the modification treatment of the polypropylene fiber, its crack resistance and segregation resistance are further improved. Combining the test results of Example 9, when polyacrylamide is not added, both the segregation resistance and crack resistance are reduced. Combining the test results of Example 10, when PAMAM and genipin are not added, its crack resistance is significantly reduced.

[0141] Combining the test results of Example 1 and Comparative Example 1, when the geopolymer is modified without forming a polyurethane buffer layer by the modification of the polyurethane prepolymer and water, its crack resistance is significantly reduced. Combining the test results of Comparative Example 2, when the carboxylated nano-silica is directly loaded after the formation of the polyurethane buffer layer during the modification of the geopolymer without being treated in the modification solution, its fluidity, segregation resistance, and crack resistance are significantly reduced. The modification solution treatment helps the chemical bonding between the carboxylated nano-silica and the geopolymer, significantly improving the fluidity. Combining the test results of Comparative Example 3, when the geopolymer in Comparative Example 3 is not loaded with nano-silica after the establishment of the polyurethane buffer layer and the modification solution treatment, its fluidity and segregation resistance are significantly reduced. In the present application, the modified geopolymer replaces part of the fly ash microspheres, which not only utilizes the ball effect of its smooth surface, but also forms a bridge between the fly ash microspheres and the aggregate due to the mass of the modified geopolymer compared with the fly ash microspheres, reducing the segregation phenomenon caused by the density difference between the two.

[0142] Combining the test results of Comparative Example 5, it can be seen that when the modified geopolymer is replaced with fly ash microbeads, its fluidity is good, but its segregation resistance and crack resistance are significantly reduced. Combining the test results of Comparative Example 4, when the modified geopolymer is replaced with an equal amount of geopolymer, its fluidity and crack resistance are significantly reduced. Referring to the test results of Comparative Example 6, when xanthan gum is not added to the admixture, both its segregation resistance and crack resistance are reduced.

[0143] This specific embodiment is only an interpretation of the present application and does not limit the present application. After reading this specification, those skilled in the art can make modifications to this embodiment without creative contributions as needed, but as long as it is within the scope of the claims of the present application, it is protected by the patent law.

Claims

1. A high-performance self-compacting and highly crack-resistant fiber-reinforced cementitious composite, characterized in that, It includes the following raw materials in parts by weight: 300 - 400 parts of cement, 50 - 70 parts of fly ash microspheres, 30 - 40 parts of silica fume, 70 - 100 parts of modified geopolymers, 250 - 300 parts of sand, 650 - 700 parts of fine aggregate, 3 - 12 parts of polypropylene fiber, 3 - 8 parts of expansive agent, 2 - 6 parts of admixture, and 100 - 120 parts of water; among them, the admixture at least includes xanthan gum, and the modified geopolymer is prepared by first subjecting the geopolymer to primary modification treatment with a polyurethane prepolymer and water, and then treating it in a modification solution containing ethylene glycol, ethylenediamine, and γ-aminopropyltriethoxysilane and loaded with carboxylated nano-silica.

2. A high-performance self-compacting and highly crack-resistant fiber-reinforced cementitious composite according to claim 1, characterized in that: The modified geopolymer is prepared through the following steps: S1. Mix the geopolymer with the polyurethane prepolymer, add water, stir, and let it stand to obtain a pre-modified geopolymer; S2. Mix ethylene glycol, ethylenediamine, and γ-aminopropyltriethoxysilane with water to obtain a modification solution, then add the pre-modified geopolymer to the modification solution and impregnate it at 50 - 60 °C for 4 - 6 h, and filter to obtain a functionalized geopolymer; S3. Mix carboxylated nano-silica, hydroxypropyl cellulose, and water to obtain a suspension; S4. Add the functionalized geopolymer to the suspension, stir at 60 - 70 °C for 1 - 2 h, filter, wash with water, and dry to obtain the modified geopolymer.

3. A high-performance self-compacting and high-crack-resistance fiber-reinforced cementitious composite according to claim 2, characterized in that: During the preparation process of the modified geopolymer, in step S1, the mass ratio of the geopolymer to the polyurethane prepolymer is 1:(0.4 - 0.6), and the addition amount of water is 5 - 10 wt% of the polyurethane prepolymer; in step S2, the mass ratio of ethylene glycol, ethylenediamine, and γ-aminopropyltriethoxysilane to water is 1:(1.2 - 1.4):(1.5 - 1.8):(4 - 6), and the mass ratio of the pre-modified geopolymer to the modification solution is 1:(4 - 5); in step S3, the mass ratio of carboxylated nano-silica, hydroxypropyl cellulose, and water is 1:(0.1 - 0.2):(2 - 3); in step S4, the mass ratio of the functionalized geopolymer to the suspension is 1:(3 - 4).

4. A high-performance self-compacting and high-crack-resistance fiber-reinforced cementitious composite according to claim 1, characterized in that: In step S3, the carboxylated nano-silica is prepared through the following method: Treat nano-silica in a sulfuric acid solution with a mass concentration of 65 - 75% for 5 - 10 min, then dry to obtain pretreated nano-silica; Mix acrylic acid and succinic acid with xylene according to a mass ratio of 1:(1 - 1.2):(2 - 2.2) to obtain an organic acid solution, then add concentrated sulfuric acid, and the addition amount of concentrated sulfuric acid is 0.5 - 1 wt% of the organic acid solution to obtain a mixed acid solution, then add the pretreated nano-silica to the mixed acid solution, reflux and react at 80 - 100 °C for 2 - 3 h, and after centrifugal separation, wash with water, wash with alcohol, and dry to obtain carboxylated nano-silica, and the mass ratio of the pretreated nano-silica to the mixed acid solution is 1:(0.3 - 0.5).

5. A high-performance self-compacting and highly crack-resistant fiber-reinforced cement-based composite material according to claim 1, characterized in that: The polypropylene fiber is added after being modified, and the modification treatment includes the following steps: 1). Subject the polypropylene fiber to plasma treatment in an oxygen atmosphere to obtain a pretreated polypropylene fiber; 2), impregnate the prepared pretreated polypropylene fiber in an ethanol aqueous solution added with γ-aminopropyltriethoxysilane, adjust the pH to 4-5, and treat it at 60-80 °C for 30-40 min to obtain a pretreated reaction solution; 3), add epichlorohydrin to the pretreated reaction solution, react at 60-70 °C for 60-90 min, then cool, filter, wash and dry to obtain modified polypropylene fiber.

6. The high-performance self-compacting and high crack-resistant fiber-reinforced cementitious composite material according to claim 5, characterized in that: When the polypropylene fiber is modified, the power during plasma treatment in step 1) is 100-200 W and the treatment time is 3-6 min; in step 2), the addition amount of γ-aminopropyltriethoxysilane is 3-5 wt% of the addition amount of the pretreated polypropylene fiber, and the mass ratio of γ-aminopropyltriethoxysilane to the ethanol aqueous solution is 1:(8-10), and the volume ratio of ethanol to water in the ethanol aqueous solution is 7:(3-4); in step 3), the addition amount of epichlorohydrin is 5-8 wt% of the addition amount of the pretreated polypropylene fiber.

7. A high-performance self-compacting and high-crack-resistance fiber-reinforced cementitious composite according to claim 5, characterized in that: When the polypropylene fiber is modified, after adding epichlorohydrin and reacting in step 3), polyacrylamide, PAMAM and genipin with a mass ratio of 1:(1.2-1.4):(0.1-0.2) are also added, and the addition amount of polyacrylamide is 3-5 wt% of the pretreated polypropylene fiber.

8. A high-performance self-compacting and high-crack-resistance fiber-reinforced cementitious composite according to claim 1, characterized in that: The admixture includes welan gum, trimethylolpropane, polycarboxylate water reducer and retarder with a mass ratio of 1:(0.6-0.8):(1.2-1.4):(0.2-0.3).

9. The high-performance self-compacting and high-crack-resistance fiber-reinforced cementitious composite material according to claim 1, wherein: The sand used is machine-made sand with a diameter of 2-10 mm, and the fine stone used is fine stone with a size of 2-5 mm.

10. A method for preparing a high-performance self-compacting and high crack-resistant fiber-reinforced cement-based composite material according to any one of claims 1-9, characterized in that: It includes the following steps: Mix and stir cement, fly ash microspheres, silica fume, sand, fine stone and modified geopolymer, and then add an expansive agent to obtain a preliminary mixture; Mix 1 / 3-1 / 2 of the admixture with water, then add the preliminary mixture, add polypropylene fiber, stir and mix, then add the remaining admixture, and stir to obtain a high-performance self-compacting and high crack-resistant fiber-reinforced cement-based composite material.

Citation Information

Patent Citations

  • Large-flow-state circumferential inverted arch thin-wall anti-crack concrete and preparation method thereof

    CN112851257A

  • Modified waste rubber powder with temperature-sensitive characteristic as well as preparation method and application of modified waste rubber powder

    CN119661966A